WHY IS THE CREDIT-DEPOSIT RATIO LOW IN KERALA ? - Narayana, D (Centre for Development Studies-WP342, 2002)
The low credit-deposit ratio of the scheduled commercial banks in Kerala has been a subject of intense debate during the last decade or so. Periodically, the state Government would raise the issue, lash out at the `negative attitude' of the banks for the lack of development of the state, the banks would counter it, and soon everyone would forget it. A systematic discussion of the various dimensions of it has been lacking. This paper makes a modest attempt to examine the issue. The C-D ratio is a product of the ratio of number of credit accounts to deposit accounts and the ratio of credit amount per account to deposit amount per account. While Kerala reports one of the highest ratio of number of credit accounts to deposit accounts, the credit amount per account is one of the lowest -deposit amount per account is comparable to the all-India level- among the states of India. The low credit amount is owing to the lack of credit deployment in industry, trade and finance. In particular, the credit amount per account in industry is very low largely because of higher share of food manufacturing and processing, other industries, and constructionwhich report low amounts of credit per account everywhere in India- in the total. Further, a comparison of the amounts per credit account in the small-scale industries with industry as a whole suggests that most of the industries in Kerala are no larger than small-scale industries. The smallscale industries in Kerala are also too small.